Factors influencing citizens’ willingness to co-produce: a study from the perspective of citizens residing in the Brazilian Federal District - Borges Júnior, José Martins; Farias, Josivania Silva (Organizações & Sociedade, 2020)
Co-production emerges as a trend in the relationship between citizens and government, enabling participation in public activities. This study verified factors that influence citizens’ willingness to co-produce public safety, health, and environmental services in the Brazilian Federal District (Distrito Federal brasileiro – DF), as well as their profile and habits. A survey adapted from the works of Löffler et al. (2008) and Alford and Yates (2016) was performed, with analyses being made from Student’s T-Test, Spearman’s Correlation Coefficient, and linear regression models. From the responses of 360 inhabitants of the DF, it was found that citizens collaborate more with health, environment, and safety services, in this order, and that in the future they intend to co-produce more than today. It was concluded that the safer a citizen feels, the lower the willingness to co-produce; and the healthier one is, the greater the willingness to co-produce. It was also found that the time devoted to volunteer activities positively influences the willingness to co-produce in these three areas. The study illustrates the behavior of citizens willing to engage in the co-production of public services, gathering information for future researchers on the subject, and exploring variables not yet considered in other Brazilian co-production studies.